2011
DOI: 10.1063/1.3548355
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Studies of Residual Damage in Low-Dose Arsenic Implanted Silicon after High-Temperature Annealing

Abstract: In order to prevent the degradation of device performance, it is necessary to detect and reduce residual damage remaining after ion implantation and annealing. In this study, we focused on the high-temperature annealing process after low-dose arsenic (As) implantation in silicon (Si) and evaluated the correlation of annealing conditions and damage by cathodoluminescence (CL) compared to Secondary Ion Mass Spectrometry (SIMS) and Junction PhotoVoltage (JPV) results. Increasing the annealing temperature with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The TO-line intensity of the only-RTA-applied sample (i.e., additional FA temperature was 0 • C) is clearly much lower than that of the reference sample, suggesting that the TO-line emission had been suppressed by non-radiative decay centers, i.e., some type of defect and/or crystal disorder. This provides strong evidence of the presence of residual damage, as we had discovered in previous studies [2]- [4]. In contrast, the TO-line intensity of the samples with additional FA at 300 • C and 400 • C gradually increased with increased annealing temperature, indicating that the vacancy-type defects mentioned above tended to be eliminated and the total number of defects was suppressed after FA.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…The TO-line intensity of the only-RTA-applied sample (i.e., additional FA temperature was 0 • C) is clearly much lower than that of the reference sample, suggesting that the TO-line emission had been suppressed by non-radiative decay centers, i.e., some type of defect and/or crystal disorder. This provides strong evidence of the presence of residual damage, as we had discovered in previous studies [2]- [4]. In contrast, the TO-line intensity of the samples with additional FA at 300 • C and 400 • C gradually increased with increased annealing temperature, indicating that the vacancy-type defects mentioned above tended to be eliminated and the total number of defects was suppressed after FA.…”
Section: Methodssupporting
confidence: 57%
“…Our previous studies, however, show that use of a rapid thermal process for heat treatment leads to residual damage [2]. In the case of low-dose implant conditions, which is Manuscript lower than the critical dose of amorphization (<10 13 cm −2 ), defects were confirmed to persist after applying RTA even with high-temperature (1100 • C) [3], [4].…”
Section: Introductionmentioning
confidence: 92%
“…c-o complex, which is origin of C-line emission as to be inversely proportional to electron conductivity (J and junction depth X j [2]. Tn order to separate these elements and confirm the reason of this phenomenon, As and B depth profiles of all samples were measured and the junction depth were evaluated from their profiles.…”
Section: Resultsmentioning
confidence: 99%
“…implanted Si after high-temperature rapid thermal annealing (RTA) by using optical characterization method, cathodoluminescence (CL), and this damage has been confIrmed to be a non-radiative decay center [2]. Moreover, our recent studies have been revealed that residual damage changes their feature according to the atmosphere during annealing.…”
Section: Introductionmentioning
confidence: 98%